2020
DOI: 10.1111/cpr.12813
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy changes in lung tissues of mice at 30 days after carbon black‐metal ion co‐exposure

Abstract: Objectives Accumulating studies have investigated the PM2.5‐induced pulmonary toxicity, while gaps still remain in understanding its toxic mechanism. Due to its high specific surface area and adsorption capacity similar to nanoparticles, PM2.5 acts as a significant carrier of metals in air and then leads to altered toxic effects. In this study, we aimed to use CBs and Ni as model materials to investigate the autophagy changes and pulmonary toxic effects at 30 days following intratracheal instillat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…In addition, nearly 20 years ago, Jakab et al confirmed that combinations of CB and formaldehyde or acrolein compromised lung host defence by suppressing killing and phagocytosis of S. aureus [36,52]. Furthermore, recent studies of CB exposure in mice studied over 30 days confirm increased autophagy after 7 days, which is reversible after 30 days [53,54]. These studies and our own confirm the importance of studying exposure to injured, stressed, or infected cells.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, nearly 20 years ago, Jakab et al confirmed that combinations of CB and formaldehyde or acrolein compromised lung host defence by suppressing killing and phagocytosis of S. aureus [36,52]. Furthermore, recent studies of CB exposure in mice studied over 30 days confirm increased autophagy after 7 days, which is reversible after 30 days [53,54]. These studies and our own confirm the importance of studying exposure to injured, stressed, or infected cells.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, nearly 20 years ago Jakab et al con rmed that combinations of CB and formaldehyde or acrolein compromised lung host defence by suppressing killing and phagocytosis of S. aureus [32,40]. Furthermore, recent studies of CB exposure in mice studied over 30 days con rm increased autophagy after 7 days which is reversible after 30 days [41,42]. These studies and our own, con rm the importance of studying exposure to injured, stressed or infected cells.…”
Section: Discussionsupporting
confidence: 63%
“…It should be mentioned that although 30 days PE is considered a long period of time in mice [ 18 , 19 ], the damage (in particular pulmonary damage) could worsen at later stages, i.e., 60 days PE or later [ 20 ]. Vice versa, it could be that following a longer period of time, enhanced tissue repair leads to decreased damage.…”
Section: Discussionmentioning
confidence: 99%